1978
DOI: 10.1177/014616727800400231
|View full text |Cite
|
Sign up to set email alerts
|

Helping as a Function of Number of Bystanders and Ambiguity of Emergency

Abstract: Previous research has shown that bystanders in groups are less likely to intervene in emergencies than bystanders who are alone (a "numbers effect"). In the present research, in one field and three lab studies, this numbers effect was stronger and there was less help when an emergency could be heard only rather than both seen and heard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 5 publications
2
29
0
Order By: Relevance
“…The difference between the two types of alarms indicate that social influence is more important for ambiguous fire cues. This conclusion is also supported by similar research about helping behaviour in emergencies [13].…”
Section: Article In Presssupporting
confidence: 81%
See 1 more Smart Citation
“…The difference between the two types of alarms indicate that social influence is more important for ambiguous fire cues. This conclusion is also supported by similar research about helping behaviour in emergencies [13].…”
Section: Article In Presssupporting
confidence: 81%
“…Research about helping behaviour has suggested that social influence may be more important for ambiguous emergencies [13]. This may also be relevant for fire emergencies.…”
Section: Introductionmentioning
confidence: 99%
“…However, no firm answer can yet be given to this question because Latané and Nida did not statistically test whether there are differences in effect sizes between emergency (high-danger) versus non-emergency (low-danger) situations. In addition, we test whether the expected effect of emergency danger on the bystander effect depends on various moderators investigated by Latané and Nida. Most importantly, Latané and Nida (1981) concluded that helping is reduced when the number of bystanders increases or when the situation is ambiguous (e.g., Clark & Word, 1974;Solomon, Solomon, & Stone, 1978). The effect occurs both in the laboratory and in the fleld (e.g., Shaffer, Rogel, & Hendrick, 1975).…”
Section: The Bystander Literature Before 1981mentioning
confidence: 99%
“…Schwartz and Clausen (1970) explained this effect by stipulating that males want to impress female bystanders. In addition, especially for highly dangerous emergencies, women tend to hand over responsibility for helping in the presence of male bystanders (Solomon, Solomon, & Stone, 1978). Thus, future research investigating more thoroughly the effects of expected danger, gender of potential helper, and number and gender of bystanders on helping behaviour will be a promising endeavour.…”
Section: Helping Behaviourmentioning
confidence: 99%